A Critical Point About Early Childhood Assessments: Validity and Reliability Issues in Teachers' Formative Assessment - Elif Buldu; Çağla Öneren Şendil (Istanbul Kültür University, 2023)
In the current study, Turkish early childhood teachers' self-reported beliefs and practices on ensuring reliability and validity on their formative assessment implementations were investigated. A total of 17 female early childhood teachers participated in this study. The data for this phenomenological study was collected through semi-structured interviews. The researchers developed some themes and categories based on participant teachers' responses about validity and reliability through constant-comparative data analysis method. The finding of the study revealed that the teachers who took part believe that obtaining valid and reliable information is critical for their assessment. Their self-reported practices, on the other hand, revealed that they have some difficulty using multiple assessment procedures with one another due to crowded classrooms and other excessive paper shuffling. The findings once again underline the importance of practical teacher training in understanding that assessment is an evidence-based process.